إستخدام أسلوبی التضمين و الأمري وأثرهما على الإتجاه والأداء المهاري بكرة اليد - شاهۆیی, أ.م.د. إبراهيم محمد مصطفى (Sulaimani Journal for Humanities, 2023)
The research aims to identify: the effect of using the embedding and commanding styles on the trend towards handball, and the effect of the embedding and commanding styles on learning the skills of handling and receiving in handball, The researcher assumed that the two styles of inclusion and command achieve an effect on the results of the research, and there is a discrepancy in the results of the post-test in favor of the style of inclusion, The researcher used the experimental approach due to its suitability to the nature of the problem. The research community was represented by the students of the second stage in the College of Physical Education, who numbered (52) male and female students distributed into two divisions. (12) students from Division (A) were chosen, the first experimental group, and applied an educational curriculum according to the inclusion style, and (12) students from Division (B), the second experimental group, applied an educational curriculum according to the commanding style, and thus the total number reached (24) students, The percentage of the sample was (46.15%), and pre-tests were conducted for the scale and skillful performance, and then the researcher started applying the program, and its duration was (4) weeks, with (2) educational units per week, and the time of each unit was (90) minutes. After completing the implementation of the educational units, the post-test was conducted, and the researcher processed the data using the (spss) program, After discussing the results, the researcher concluded that: The inclusion and commanding styles have a positive effect on the change towards learning my skill under study, and the inclusion style outperformed the commanding style in the positive change of the trend towards learning my skill under study, And the inclusion style is better compared to the commanding style in terms of the effect on learning my skill under study, The researcher recommended using style Inclusion because of its positive impact on the development of students' skills, style Inclusion in learning the rest of the basic handball skills, and the need to use style inclusion and comparison with the rest styles Modern in teaching my skill is under research,
Keywords: embedding style; commanding style; trend towards handball; skillful performance